Analisis Penyaluran Dana Zakat Terhadap Kesejahteraan Mustahik Menggunakan Metode CIBEST (Center For Islamic Business And Economuc Studies) (Studi kasus BAZNAS Kota Jambi) - Zalfa Rianda; Nurida Isnaeni; Ary Dean Amri (JOURNAL OF SHARIA ECONOMICS, 2024)
This study aims to analyze the distribution of zakat funds through the Jambi City Care program for business capital assistance and business equipment with a focus on knowing changes in the level of income welfare and the level of spiritual welfare of mustahik before and after receiving productive zakat assistance, through the CIBEST (Center For Islamic Business and Economis Studies) approach. This research uses descriptive quantitative methods, the type of data used in this research is primary data obtained through interviews and distributing questionnaires and secondary data in the form of data on mustahiks who receive productive zakat assistance from BAZNAS Jambi City. Respondents in this study amounted to 20 mustahik households. The analysis method used in this research is the CIBEST model and the Wilcoxon Difference Test. The results of this study indicate that there are significant changes before and after receiving productive zakat funds from BAZNAS Jambi City. Based on the calculation of the CIBEST index value in 20 mustahik households before the productive zakat fund assistance, it shows that 30% of mustahik households live in prosperous conditions, 65% are in meteriil poverty, 5% spiritual poverty and 0% absolute poverty. While after receiving productive zakat assistance shows that 100% of mustahik households live in a prosperous condition, 0% in meteriil poverty, 0% spiritual poverty, 0% absolute poverty.